Epidermotropic Cutaneous Metastasis of Colonic Adenocarcinoma Presenting as a Sister Mary Joseph Nodule. (28th November 2022) - Jimenez, Antonio; Winsett, Frank; Kelly, Brent; Goodwin, Brandon
Abstract: The Sister Mary Joseph nodule is a metastatic umbilical lesion that is seen in 1%–3% of intra-abdominal and pelvic malignancies. Cutaneous metastasis of visceral malignancies is rare and has characteristic dermal or subcutaneous involvement on histopathologic examination. Epidermotropism is described as the migration of malignant cells into the epidermis and is an unusual finding in intra-abdominal malignancies and cutaneous metastases. An 81-year-old woman with a past medical history of colorectal adenocarcinoma presented to the dermatology clinic for evaluation of an enlarging, denuded umbilical mass. A tangential biopsy was obtained and sent for histopathologic examination. Histopathologic analysis demonstrated infiltration of atypical, pleomorphic cells in the dermis with spread into the epidermis, consistent with epidermotropism. An immunohistochemical panel was performed and was consistent with cutaneous metastasis of the patient's underlying adenocarcinoma. We present a case of epidermotropic cutaneous metastasis of colorectal adenocarcinoma presenting as a Sister Mary Joseph nodule, an extremely rare occurrence that has not been well-documented in the literature.